KINEMATIC ANALYSIS OF SPATIAL 3-RPS PARALLEL MECHANISM - GAO HongWei (Jixie qiangdu)
the coupling relationship between the position of the moving platform and the attitude parameters is derived from the joint constraints of the spatial 3-RPS parallel mechanism, and the independent parameters used to describe the configuration of a mechanism is given. The geometric constraint of the mechanism is established by using the equal motion condition, and the inverse equation of the mechanism position is obtained. The relation between the velocity and acceleration between the components is established by using the first and two order derivatives of the constraint equations, thus avoiding the occurrence of composite joint variables in the equations of motion. The explicit relationship between velocity and acceleration among components is obtained. It proves that this method has the advantages of high computational efficiency and is helpful for the rapid solution and dynamic simulation of mechanism problems.